PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, SALES GROWTH TERHADAP KINERJA KEUANGAN(Studi Kasus Pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Sifa Anggraeni; Iman Hariono; Erfan Erfiansyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), leverage, and sales growth on financial performance in Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The background of this research lies in the fluctuating financial performance and the uneven implementation of Corporate Social Responsibility. CSR is measured using disclosure scores based on the Global Reporting Initiative (GRI) guidelines, leverage is measured using the Debt to Equity Ratio, sales growth is measured by the annual percentage change in sales compared to the previous year, and financial performance is measured using Return on Assets (ROA). This research employs a quantitative method with purposive sampling, involving 14 companies as the research sample. The data used are secondary data obtained from annual reports and sustainability reports. The data analysis technique applied is multiple linear regression, processed using SPSS version 25. The results indicate that, partially, Corporate Social Responsibility has no significant effect, leverage has a significant negative effect, and sales growth has no significant effect on financial performance. Simultaneously, CSR, leverage, and sales growth significantly influence financial performance. These findings provide important implications for companies to pay greater attention to both internal and external factors in improving their financial performance.